The impact of COVID-19 on trauma and orthopaedic patients requiring surgery during the peak of the pandemic: a retrospective cohort study - Nicola D Mackay (Bone & Joint Open, 2020)
Aims: COVID-19 represents one of the greatest global healthcare challenges in a generation. Orthopaedic departments within the UK have shifted care to manage trauma in ways that minimize exposure to COVID-19. As the incidence of COVID-19 decreases, we explore the impact and risk factors of COVID-19 on patient outcomes within our department. Methods: We retrospectively included all patients who underwent a trauma or urgent orthopaedic procedure from 23 March to 23 April 2020. Electronic records were reviewed for COVID-19 swab results and mortality, and patients were screened by telephone a minimum 14 days postoperatively for symptoms of COVID-19. Results: A total of 214 patients had orthopaedic surgical procedures, with 166 included for analysis. Patients undergoing procedures under general or spinal anaesthesia had a higher risk of contracting perioperative COVID-19 compared to regional/local anaesthesia (p = 0.0058 and p = 0.0007, respectively). In all, 15 patients (9%) had a perioperative diagnosis of COVID-19, 14 of whom had fragility fractures; six died within 30 days of their procedure (40%, 30-day mortality). For proximal femoral fractures, our 30-day mortality was 18.2%, compared to 7% in 2019. Conclusion: Based on our findings, patients undergoing procedures under regional or local anaesthesia have minimal risk of developing COVID-19 perioperatively. Those with multiple comorbidities and fragility fractures have a higher morbidity and mortality if they contract COVID-19 perioperatively; therefore, protective care pathways could go some way to mitigate the risk. Our 30-day mortality of proximal femoral fractures was 18.2% during the COVID-19 pandemic in comparison to the annual national average of 6.1% in 2018 and the University Hospital Coventry average of 7% for the same period in 2019, as reported in the National Hip Fracture Database. Patients undergoing procedures under general or spinal anaesthesia at the peak of the pandemic had a higher risk of contracting perioperative COVID-19 compared to regional block or local anaesthesia. We question whether young patients undergoing day-case procedures under regional block or local anaesthesia with minimal comorbidities require fourteen days self-isolation; instead, we advocate that compliance with personal protective equipment, a negative COVID-19 swab three days prior to surgery, and screening questionnaire may be sufficient.